Pengembangan Sistem Itinerary Pendakian Gunung di Jawa Timur Pada Perangkat Bergerak (Studi Kasus: Gunung Arjuno dan Welirang) - Ary Budi Laksono; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mountain climbing activities in Indonesia have been around for a long time, this activity includes outdoor activities that are full of risks, even some mountains have difficulty levels and special equipment is needed to climb it, but it is not uncommon for accident cases to occur, caused by ignorance and unconsciousness of the activists will be faced with risks, so as not to make maximum preparation, with this application climbers can manage time management, accommodation and logistics for the smooth and safe mountaineering. This application was developed on Android mobile devices using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to determine climbing routes based on criteria for terrain difficulties, climbing time and number of visitors. In this application available information on estimated costs, logistics information and directions to the ascent base camp location using latitude and longitude from the Google API. The results of the blackbox test on this application show that the functional features are 100% valid, in addition to the blackbox testing, usability testing is also done to find out the usefulness of the application through a questionnaire to users that shows 83.9011% and the results of validation algorithms that show the algorithm are well implemented.